(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
The incidence of cancer during pregnancy is increased in recent years. The rate of increase is attributed to, not only higher rate of cancer in general, but also to a delay in child-bearing age. We report such an uncommon case of pregnancy with malignant ovarian tumor. Our case is a 26 years 2nd gravida presented at 32 weeks of her pregnancy with acute abdomen in emergency department of BBMH, USTC. A thorough clinical examination and investigation revealed pregnancy with ovarian tumor with sub-acute intestinal obstruction. The patient is treated with surgery followed by chemotherapy. Now the patient is normal without evidence of disease upto 12 months with a healthy Baby. The case is selected due to the rarity of the condition and the diagnostic dilemma when it presents during pregnancy. JCMCTA 2016 ; 27 (2) : 84 - 86